2015
DOI: 10.1177/1947603515574838
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chondrogenic Progenitor Populations Associated with Aging and Osteoarthritis

Abstract: Chondrogenic progenitor populations, including mesenchymal stem cells, represent promising cell-based transplantation or tissue engineering therapies for the regeneration of damaged cartilage. Osteoarthritis (OA) predominantly affects the elderly and is a leading cause of disability worldwide. Advancing age is a prominent risk factor that is closely associated with the onset and progression of the disease. Understanding the influence that aging and OA have on chondrogenic progenitor cells is important to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…Also, there is no hint in the literature that, vice versa, healthy but not OA chondrocytes would express RUNX2, RUNX3, or MEF2C. Regarding MPCs, we and many other groups have documented that hypertrophy develops irrespective of whether the bone marrow aspirates were derived from OA patients or non-OA patients (Scharstuhl et al, 2007;Dexheimer et al, 2011;Brady et al, 2015). Nevertheless, unless data are repeated with cells from healthy donors, the OA background should be kept in mind.…”
Section: Discussionmentioning
confidence: 92%
“…Also, there is no hint in the literature that, vice versa, healthy but not OA chondrocytes would express RUNX2, RUNX3, or MEF2C. Regarding MPCs, we and many other groups have documented that hypertrophy develops irrespective of whether the bone marrow aspirates were derived from OA patients or non-OA patients (Scharstuhl et al, 2007;Dexheimer et al, 2011;Brady et al, 2015). Nevertheless, unless data are repeated with cells from healthy donors, the OA background should be kept in mind.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have suggested that cells derived from C dp had higher proliferation and differentiation potential in comparison to C sp cells . This difference in observations could be attributed to the disease state of the tissue collected in prior studies, the anatomic site of collection, methods of digestion, and culture conditions …”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that cartilage specimens assessed in this study exhibited Outerbridge grade 1–2 OA (cartilage with swelling or some small fissures on the surface), and were obtained from an older patient population (age group: 45–76 years). The effect of ageing and OA on adult progenitor population in different zones of cartilage has been scarcely studied, and the limited literature available presents conflicting results . Rolauffs et al has previously reported that cell densities in superficial zone of non‐degenerate (Collins0‐I) and degenerate femoral condyle cartilage (Collins II) were 9.5 million cells per gram, and 15 million cells/gram and significantly differ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations